Beyond sight : Victor Tan. - Ng, Grace Yue Sum. (2009)
“Beyond Sight” (Duration: 8 min 18 s) is a video documentary about Victor Tan Wee Tar, a 28-year-old blind sculptor. The documentary attempts to show how Victor functions as a sculptor and student at the La Salle-SIA College of the Arts despite his disability. Using a combination of personal narrative and interviews, the video hopes to reveal some of Victor’s personal thoughts and some issues and problems that he faces as an artist. The video begins with a montage that shows Victor working on a sculpture. This is mixed with shots of one of Victor’s completed sculptures. Accompanying the montage are several soundbites praising Victor’s capability as a sculptor. As the montage ends, we see Victor on his way to school. Over visuals of him travelling to school, Victor describes how he became blind and how he decided to pick himself up to start a new life as a student with La Salle-SIA College of the Arts. At the college, the video shows him attending classes with the rest of the students. Later, Victor demonstrates how he sculpts. Relying on his memory, Victor is able to visualise his sculptures before he sculpts and, using materials that are highly tactile in nature, he then proceeds to sculpt highly realistic human figures. A short montage on one of his works follows. In this beautifully-shot montage, Victor’s voice drifts in to explain that the use of wire in his work represents his continuous interaction with other people around him. This links to the next segment, which shows how interaction is part and parcel of his learning process. Victor reveals that for his theory classes, he needs the help of his friends to read him the necessary readings. Also in this segment, his classmates and lecturers give their opinions of him as a friend, student and artist, As the video draws to a close, the documentary probes deeper into Victor’s psyche. In a last interview, Victor reveals his frustration at being labelled a “disabled artist”. What he wants is for the audience to judge his works based solely on his ability. The audience should disregard his blindness when judging his art.